2002
DOI: 10.1159/000048234
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Adenylate Cyclase Activating Polypeptide and Neuropeptide Y Regulation of Gonadotropin Subunit Gene Expression in Tilapia: Role of PKC, PKA and ERK

Abstract: There is ample information on the hypophysiotropic function of pituitary adenylate cyclase-activating polypeptide (PACAP) and neuropeptide Y (NPY) in fish as in mammals, although evidence as to their direct effects on gonadotropic cells is scarce. We have previously reported that NPY and PACAP38 augment gonadotropin-releasing hormone (GnRH)-induced expression of glycoprotein α (α) subunit gene in the teleost fish, tilapia. The aim of the present study was to elucidate possible direct effects of these peptides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…NPY dose-dependently increased cellular level of phosphorylated extracellular signal-regulated protein kinase (pERK1/2) in cultured cells (Gur et al, 2002). It has been shown that food deprivation increases neuronal level of pERK1/2 in the hypothalamic paraventricular nucleus (PVN) of mice (Ponsalle et al, 1992) and rat (Ueyama et al, 2004; Lee et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…NPY dose-dependently increased cellular level of phosphorylated extracellular signal-regulated protein kinase (pERK1/2) in cultured cells (Gur et al, 2002). It has been shown that food deprivation increases neuronal level of pERK1/2 in the hypothalamic paraventricular nucleus (PVN) of mice (Ponsalle et al, 1992) and rat (Ueyama et al, 2004; Lee et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The present study now provides evidence that these changes in NGF-regulated adrenergic expression in PC-12 cells are at least in part mediated through an increase in PNMT promoter-driven gene transcription. Furthermore, although NGF activates a number of intracellular signaling pathways, including those of PKA (Schubert et al, 1977;Gur et al, 2002;Vaudry et al, 2002), PKC (Hama et al, 1986;Gur et al, 2002;Sakai et al, 2004), p38 MAPK (Xing et al, 1996;Dohi et al, 2002;Gur et al, 2002;Vaudry et al, 2002;Sakai et al, 2004), and ERK1/2 MAPK (Xing et al, 1996;Dohi et al, 2002;Gur et al, 2002;Vaudry et al, 2002;Sakai et al, 2004), only the ERK1/2 MAPK pathway seems involved in PNMT promoter activation by NGF. In the case of PKA and PKC signaling, we provide direct evidence that activation of these pathways produces an incremental rise in NGF-mediated PNMT promoter-driven luciferase expression (Figs.…”
mentioning
confidence: 99%
“…In spite of this, the response of NPY-containing nuclei in the forebrain of teleost following gonadectomy and gonadal steroid replacement remained unexplored. Among teleosts, tilapia may be considered as a suitable model with which to address this issue, because background information on 1) its GnRH system (Parhar et al, 1996a;Parhar, 1997), 2) the response of the system to castration and testosterone replacement , 3) the absence of ER␣ in the GnRH neurons , and 4) the role of NPY in GnRH induced up-regulation of the GtH mRNA subunits (Yaron et al, 2001(Yaron et al, , 2003Gur et al, 2002) is already available. Because information about the organization of the NPY neuronal system in this fish is not available, we first describe the distribution of the NPY-immunoreactive (-ir) system in the forebrain of sexually mature male tilapia (Oreochromis mossambicus).…”
mentioning
confidence: 99%